Analisa Rasio Keuangan Terhadap Pertumbuhan Laba Perusahaan Sektor Kesehatan - Risnawati, Risnawati; Juwari, Juwari; Susilowati, Dwi; Sudjinan, Sudjinan (MEDIA RISET EKONOMI [MR.EKO], 2024)
The purpose of this study was to determine and analyze the partial effect of financial performance which includes the variables Current Ratio, Debt To Equity Ratio, and Return On Asset on Profit Growth in Health Industry Sector Companies. The population and samples in this study were all health sector companies listed on the Indonesia Stock Exchange as many as 21 companies. The data analysis method used in this research is quantitative analysis method, the analysis is carried out using classical assumption testing, multiple linear regression analysis, and hypothesis testing (t test). Based on the results of the hypothesis test (t test), Current Ratio has a positive and insignificant effect on Profit Growth (Y) in Health Sector companies. Debt to Equity Ratio has a positive and significant effect on Profit Growth in Health Sector companies. Return on Asset has a positive and significant effect on Profit Growth in Health Sector companies. Based on the partial test results (t test) it can be concluded that of the three variables, Debt to Equity Ratio has a dominant influence on Profit Growth because it has the largest t value and partial r.